(untitled) (Scientific journal of the Fergana State University, 2023)
In the article the author summarizes the importance and expediency of teaching through innovative technologies. The main purpose of teaching foreign language is communicative activity of students or acquiring the knowledge of foreign language. The task of the teacher is to reinforce the work of each student in the learning process and to come up with a situation for their creativity. There are many non-standard forms of work of the teacher activating attention and increasing the students’ interest in learning foreign languages.